2020
DOI: 10.1111/jcmm.15040
|View full text |Cite|
|
Sign up to set email alerts
|

Long non‐coding RNA‐H19 stimulates osteogenic differentiation of bone marrow mesenchymal stem cells via the microRNA‐149/SDF‐1 axis

Abstract: Bone defects resulting from non-union fractures or tumour resections are common clinical problems. Long non-coding RNAs (lncRNAs) are reported to play vital roles in stem cell differentiation. The aim of this study was to elucidate the role of lncRNA-H19 in osteogenic differentiation of bone marrow mesenchymal stem cells (BMMSCs). Following the establishment of an osteogenic differentiation model in rats, the expression of H19, microRNA-149 (miR-149) and stromal cell-derived factor-1 (SDF-1) was measured by RT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 30 publications
3
30
0
Order By: Relevance
“…Our results were consistent with Zeng et al [22]. H19 plays a critical role in the differentiation of many vital organs and plays pivotal roles in the differentiation of mesenchymal stem cells [23][24][25][26]. Keniry et al [27] found that H19 can enhance the expression level of RUNX2 to promote bone regeneration.…”
Section: Discussionsupporting
confidence: 92%
“…Our results were consistent with Zeng et al [22]. H19 plays a critical role in the differentiation of many vital organs and plays pivotal roles in the differentiation of mesenchymal stem cells [23][24][25][26]. Keniry et al [27] found that H19 can enhance the expression level of RUNX2 to promote bone regeneration.…”
Section: Discussionsupporting
confidence: 92%
“…LncRNA NEAT1 promotes osteogenic differentiation of human BMSCs (hBMSCs) by modulating miR-29b-3p/BMP1 [ 21 ]. LncRNA H19 is a member of the lncRNA family, and studies have shown that up-regulated H19 facilitates osteogenic differentiation of BMSCs by facilitating stromal cell-derived factor 1 (SDF-1) through miR-149 [ 22 ]. Besides, H19 strengthens osteogenic differentiation of BMSCs by regulating the miR-140-5p/SATB2 axis [ 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…After establishing an in vitro rat-derived osteogenic differentiation model, Li et al [57] compared H19 expression between cells cultured in osteogenic condition compared with control, revealing its increased expression in differentiated cells with respect to cells without treatment. Additional experiments showed that H19 overexpression by H19 mimic treatment induces a relevant increase of ALP activity and calcium nodule formation, as well as an increase of osteogenic-related protein levels (i.e., ALP, OCN, RUNX2, and OSX), as opposed to cells transfected with shRNA.…”
Section: Lncrnas As Positive Regulatorsmentioning
confidence: 99%